Directing group assisted rhodium catalyzed meta-C–H alkynylation of arenes. Issue 19 (29th April 2022) - Sasmal, Sheuli; Prakash, Gaurav; Dutta, Uttam; Laskar, Ranjini; Lahiri, Goutam Kumar; Maiti, Debabrata
Abstract : An unprecedented report on Rh-catalyzed meta -C–H alkynylation of arenes, aided by a weakly coordinating cyano-based directing template, was developed using bromoalkynes as the coupling partner. Abstract : Site-selective C–H alkynylation of arenes to produce aryl alkynes is a highly desirable transformation due to the prevalence of aryl alkynes in various natural products, drug molecules and in materials. To ensure site-selective C–H functionalization, directing group (DG) assisted C–H activation has been evolved as a useful synthetic tool. In contrast to DG-assisted ortho -C–H activation, distal meta -C–H activation is highly challenging and has attracted significant attention in recent years. However, developments are majorly focused on Pd-based catalytic systems. In order to diversify the scope of distal meta -C–H functionalization, herein we disclosed the first Rh(i ) catalyzed meta -C–H alkynylation protocol through the inverse Sonogashira coupling reaction. The protocol is compatible with various substrate classes which include phenylacetic acids, hydrocinnamic acids, 2-phenyl benzoic acids, 2-phenyl phenols, benzyl sulfonates and ether-based scaffolds. The post-synthetic modification of meta -alkynylated arenes is also demonstrated through DG-removal as well as functional group interconversion.